Relationship between socio-demographic profile and the career preference of incoming college freshmen students - Aguilar, Maricarl S.; Mata, Hans Dominik A.; Placio, Nica V. and Portugal, Ronnie G. 4 0 16; 5
u
Thesis: (Bachelor of Secondary Education with Specialization in Social Studies) - Pamantasan ng Lungsod ng Maynila, 2014.
Keywords: 2 -- 0; 6; 20; 20; 2